Lcz696 Alleviates Myocardial Fibrosis After Myocardial Infarction Through the sFRP-1/Wnt/β-Catenin Signaling Pathway - Liu, Jing; Zheng, Xuehui; Zhang, Chen; Zhang, Chunmei; Bu, Peili (Frontiers in Pharmacology, 2021)
Background:Heart failure (HF) is invariably accompanied by the development of cardiac fibrosis, a form of scarring that increases muscular tissue rigidity and decreases cardiac contractility. Treatment options to block or reverse fibrosis are limited. Lcz696 (ARNI, angiotensin receptor–neprilysin inhibitor, sacubitril/valsartan) shows an inhibitory effect on fibrosis after myocardial infarction; however, the underlying signaling mechanisms are poorly understood. The Wnt/β-catenin signaling pathway is activated after myocardial infarction (MI) and participates in the process of myocardial fibrosis. Methods:This study aimed to investigate whether lcz696 inhibits the Wnt/β-catenin signaling pathway, thereby playing a cardiac protective role in MI. We also analyzed whether lcz696 affects the expression of sFRP-1 (secreted frizzled-related protein 1), an inhibitor of Wnt/β-catenin signaling pathway. In vivo, a mouse model of MI was constructed by ligating the left coronary artery. After a week of adaptive feeding, the surviving mice were administered 60 mg/kg ARNI or 30 mg/kg valsartan for 4 weeks. In vitro, primary cardiac fibroblasts (CFS) were stimulated with angiotensin II (Ang II) and cultured with lcz696 (ARNI) or valsartan (VAL). To further explore the role of sFRP-1, we used the sFRP-1 inhibitor way316606. Results: Our data show that lcz696 could significantly improve myocardial fibrosis and protect cardiac function, with superior efficiency than valsartan. Of note, the WNT/β-catenin signaling pathway was inhibited and the expression of sFRP-1 increased after lcz696 or VAL treatment. Additionally, we found that the influence of lcz696 on β-catenin was related to the expression of sFRP-1. Conclusion: Our study demonstrates, for the first time, that ARNI inhibits the WNT/β-catenin signaling pathway via the promotion of the expression of sFRP-1, thereby playing a cardiac protective role. Thus, our study provides a new therapeutic approach to improve myocardial fibrosis and prevent myocardial remodeling.